"It brought hope and peace in my heart:" Caregivers perceptions on kangaroo mother care services in Malawi - Alinane Linda Nyondo-Mipando; Mai-Lei Woo Kinshella; Sangwani Salimu; Brandina Chiwaya; Felix Chikoti; Lusungu Chirambo; Ephrida Mwaungulu; Mwai Banda; Laura Newberry; Jenala Njirammadzi; Tamanda Hiwa; Marianne Vidler; et al. (BMC, 2020)
Abstract Background Kangaroo mother care (KMC) is an effective intervention for preterm and low birth weight infants. Effective implementation of KMC relies on a multidisciplinary team centering on the newborn's caregiver, who delivers care with support from health care workers. This study explored the experiences of caregivers on the implementation of KMC. Methods We conducted a descriptive qualitative study in the phenomenological tradition, an interpretative approach to describe the caregivers' lived experience with KMC at four health facilities in Malawi from April and June 2019 through 10 non-participatory observations and 24 face-to-face interviews. We drew a purposive sample of 14 mothers, six fathers, three grandmothers, and one grandfather of infants receiving KMC in three secondary and one tertiary level hospitals. Data were analyzed following a thematic approach. Results Caregivers had limited information on KMC before admission with most of the information learned from peers rather than medical professionals. Stories of positive outcomes following KMC contributed to a shift in perceptions of premature babies and acceptability of KMC as an effective intervention. Unintended consequences resulting from admission due to KMC disrupts responsibilities around the home and disrupts economic activities. Gender division of roles exists with the implementation of KMC and a mother's support networks are crucial. Conclusion Kangaroo mother care is feasible and acceptable among caregivers. KMC babies are described more positively with the potential to grow into strong and healthy children. KMC remains focused on the mother, which undervalues the important roles of her support network. A change in the nomenclature from kangaroo mother care to kangaroo care would include fathers and others delivering care.